CLINICAL SYMPTOMS OF ALIMENTARY INFERTILITY IN PRODUCTIVE COWS (International Engineering Journal For Research & Development, 2021)
This article describes the clinical signs of alimentary infertility in cows, in which the diagnosis of obstetric and gynecological diseases.